Oil filter modification for biodiesel–fueled engine: A pathway to lubricant sustainability and exhaust emissions reduction. (February 2015) - Gulzar, M.; Masjuki, H.H.; Kalam, M.A.; Varman, M.; Rizwanul Fattah, I.M.
Highlights: Deposition of NaOH on oil filter was tested for palm biodiesel (PME) fueled CI engine. Strong base filter helps in maintaining the lubricant quality for longer oil sustainability. Lubricant, conditioned by strong base filter element, shows better wear resistance. Strong base filter helps in improving engine performance and reducing engine exhaust emissions. Abstract: The widespread use of biodiesel in internal combustion engines promotes frequent lubricant drain intervals which in turn affects lubricant sustainability and engine performance. In this research two endurance tests were carried out to evaluate the novel approach of strong base oil filter with palm biodiesel (PME) fueled single-cylinder diesel engine. The effects of strong base filter on lubricant rheology, piston ring/cylinder wear losses, engine performance and exhaust emissions were investigated. The results of long duration engine testing showed that the strong base filter improved the lubricant's physical and tribological characteristics. Tribo-testing, using high stroke reciprocating test rig, proved that the mechanical energy losses due to piston ring-cylinder interaction were reduced significantly. Finally, the engine performance and exhaust emissions analysis for strong base filter testing showed an improvement in engine performance, average decrease of 2.78% in carbon monoxide (CO) emissions, 7.18% reduction in hydrocarbon (HC) emissions and 3.3% reduction in smoke opacity at full load engine conditions.